American journal of education (Chicago, IL : University of Chicago Press, 2020)
1.Salir Adelante: Collaboratively Developing Culturally Grounded Curriculum with Marginalized Communities.JOSEPH LEVITAN, KAYLA M. JOHNSON In this article we discuss a collaborative research project meant to ground community members' voices in curriculum design. We argue that performing collaborative research with students and parents can better inform curriculum design decisions, particularly for communities whose identities, knowledge(s), and ways of being have been historically marginalized. Building from the culturally responsive curriculum literature, we have developed a culturally grounded curriculum development approach. We illustrate the approach through discussing a case of its development and implementation with an educational nongovernmental organization (NGO) that provides access to secondary school for Quechua (Indigenous) young women in Peru. This article reflexively reports the process of the NGO's collaborative inquiry project to cocreate meaningful educational opportunities with the students and parents. We then discuss dilemmas of interpretation that arose when incorporating community voices into curricular decisions, and how the collaborative curriculum approach can apply to formal and nonformal learning spaces in other contexts.--2.The Organizational Landscape of Schools: School Employees' Conceptualizations of Organizations in Their Environment. ANDREA PRADO TUMA A growing body of evidence suggests that schools' partnerships with neighborhood organizations can improve educational outcomes, but less is known about how educators, who play a crucial role in procuring, carrying out, and maintaining such partnerships, conceptualize the different organizations in their environment. This study uses data from 52 qualitative interviews to systematically examine how educators working in different types of urban schools and neighborhoods make sense of their interactions with external organizations. The findings contribute to scholarship on school-community partnerships by demonstrating that neighborhood organizations provide unique benefits to educators, brokering relationships between the school and the community and generating opportunities for the co-creation of resources by educators and community members. Furthermore, the study shows that educators' sense-making about the local organizational landscape is related both to the availability of geographically proximate organizations and to where students and families reside.--3.A Tale of Racial Fortuity: Interrogating the Silent Covenants of a High School's Definition of Success for Youth of Color. JASON SALISBURY This qualitative case study employing a critical race theory methodology uses Derrick Bell's conceptualization of racial fortuity to examine the ways leaders at Carver High School responded to accountability pressures related to supporting students of color. Findings highlight how school leaders' espoused racially just improvement initiatives and definitions of success were actually instantiations of racial fortuity where students of color were forced to involuntarily sacrifice their educational opportunities while leaders were positioned as the primary beneficiaries of this equity-minded work. The implications highlight the need for leaders to bring communities and students of color into school improvement efforts intended to advance racially just educational opportunities for youth of color.--4.My Voice Matters": High School Debaters' Acquisition of Dominant and Adaptive Cultural Capital.KARLYN J. GORSKI Low-income, racial/ethnic minority youth in under-resourced schools have certain opportunities to acquire cultural capital that is valued in dominant institutional contexts. I use observational data from 6 months of debate practices and competitions with two teams in the Chicago Debate League, as well as interviews with 12 debaters and 2 coaches, to show that debate participation can contribute to participants' acquisition of two forms of cultural capital. I argue that debaters demonstrate dominant cultural capital through demanding critical feedback and analyzing complex ideas. I further document how debaters develop "adaptive cultural capital, " or cultural capital that dominant institutions demand of them but that is not required of members of dominant social groups. Here, adaptive cultural capital is illustrated through debaters' ability to face failure with resilience. These findings contribute to sociological understanding of how schools influence students' acquisition of diverse forms of cultural capital.